Effectiveness of a Community and School-Based Intervention to Control and Prevent of Tobacco Use in Adolescents: A Field Randomized Controlled Trial - Fariba KHAYYATI; Mohammad ASGHARI JAFARABADI; Masoud LOTFIZADEH; Asrin KARIMI; Khaled RAHMANI (Tehran University of Medical Sciences, 2019)
No Abstract###